Dating copper-based archaeological materials using the voltammetry of microparticles - Doménech-Carbó, Antonio (2015)
The voltammetry of microparticles, an electrochemical technique providing information on the composition of archaeological materials using an essentially non invasive analysis [1,2] was previously applied for dating lead-based materials [3,4]. It is described the application of this methodology for dating copper-based archaeological materials based on a theoretical model for long term metal corrosion [5]. Dating is based on the measurement of the voltammetric signals of cuprite and tenorite formed as a corrosion products in artifacts submitted to aging in atmospheric environments with no exigent corroding conditions. Assuming that the composition and conditions of aging can be considered as similar for all samples, and that the corrosion proceeded uniformly during the entire corrosion time, the time variation of the tenorite/cuprite ratio fits to a potential law from calibration using a set of copper-based coins. As a result, absolute dating can be obtained. References [1] Doménech, A.; Doménech, M.T.; Costa, V. Electrochemical methods applied to archaeometry, conservation and restoration, (Scholz, F. Edit.) Springer, Berlin-Heidelberg, 2009. [2] Doménech, A.; Doménech, M.T.; Pasíes, T.; Bouzas, M.C. Electroanalysis, 2011, 23, 2803-2811. [3] Doménech, A.; Doménech, M.T.; Peiró, M.A. Analytical Chemistry 2011, 83, 5639-5644. [4] Doménech, A.; Doménech, M.T.; Peiró, M.A.; Martínez, I.; Barrio, J. Journal of Solid State Electrochemistry 2012, 16, 2349-2356. [5] Doménech, A.; Doménech, M.T.; Pasíes, T.; Bouzas, M.C. Electroanalysis, 2012, 24, 1945-1955.